Association between deep vein thrombosis and stent patency in symptomatic iliac vein compression syndrome: Systematic review and meta-analysis - Rodrigues, Lenize da Silva [UNESP]; Bertanha, Matheus [UNESP]; El Dib, Regina; Moura, Regina [UNESP] (Elsevier, 2020)
Background: The study intended to evaluate stent primary patency rates for patients with iliac vein obstruction related with iliac vein compression syndrome according to clinic presentation. Methods: A systematic review and meta-analysis was conducted of studies that compared: unexposed patients with nonthrombotic iliac vein lesion (NIVL, group 1) vs exposed patients with iliac acute deep vein thrombosis (DVT, group 2); and NIVL (group 1) vs exposed patients with iliac vein obstruction and post-thrombotic syndrome (PTS, group 3). The following databases were searched: EMBASE, PubMed, Web of Science, Scopus, SciELO, and LILACS. Two reviewers independently selected the potential studies and extracted data. The pooled odds ratio (OR) and 95% confidence interval (95% CI) are shown for each outcome. Results: Five studies with a total of 1050 participants and 1169 lower limbs were included. Five hundred eighty-eight lower limbs presented NIVL (50.3%), 91 lower limbs presented acute DVT (7.7%), and 490 lower limbs presented PTS (42%). The endovascular technical success rate of stenting did not differ in any of the groups: 99.6% in NIVL, 94.5% in acute DVT, and 96.5% in PTS (P = .0632). The primary stent patency rates in the 6-month follow-up were 98.3% in NIVL vs 90.9% in PTS, with a statistical difference showing reduced stent patency rates in PTS (OR, 0.17; 95% CI, 0.06-0.48; P = .0008; I2 = 0%), and 100% in the NIVL group vs 91.6% in acute DVT, with no statistical difference (OR, 0.30; 95% CI, 0.06-2.32; P = .30; I2 = 0%). The primary stent patency rates in the 12-month follow-up were 94.6% in NIVL vs 84.1% in PTS, with a statistical difference showing decreases stent patency rates in the PTS group (OR, 0.29; 95% CI, 0.14-0.63; P = .0008; I2 = 0%), and 91.1% in NIVL vs 90.9% in acute DVT, with no statistical difference (OR, 1.03; 95% CI, 0.26-4.07; P = .96; I2 = 0%). Conclusions: There is no statistical difference for the stent primary patency rates when the treatment is conducted in NIVL as compared with acute DVT lower limbs (at 6 and 12 months); therefore, other criteria must be considered for the indication of this treatment in NIVL patients. However, because there were better results of stent primary patency rates for NIVL vs PTS patients, this finding favors the treatment of acute DVT instead of PTS in lower limbs, once PTS renders smaller stent patency rates at 6 and 12 months.
Keywords: Cockett syndrome; Deep venous thrombosis; Iliac vein compression syndrome; May-Thurner syndrome; Stent patency; Systematic review